Analisis Faktor-Faktor Penguatan dan Pemerataan Ekonomi Masyarakat Desa Pesisir Danau Toba,Kecamatan Ajibata - Eko Deswin Miechaels Siringo-Ringo; Arwin Tannuary (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
A strong country starts from the condition of each strong village. The problem that becomes the object of this research is the weakness of the economy and the inequality of the village economic level in Ajibata District which is around the coast of Lake Toba. Ajibata District consists of 9 villages and 1 kelurahan, namely Pardomuan Motung, Pardamean Ajibata, Pardomuan Ajibata, Parsaoran Ajibata, Motung, Horsik, Sigapiton, Pardamean Sibisa, Parsaoran Sibisa, Sirungkungon. Each village and kelurahan has its own characteristics and potential, but according to available data, the economic condition of this village is very uneven, the creative economy of the village community is also very weak and low. When viewed from the predicate of Lake Toba as an international tourist center with the brand image of Monaco Of Asia, this condition is very unfavorable and unnatural. The purpose of this study was to determine the factors that strengthen and equalize the village economy. The analytical technique used is the Miles and Huberman approach. The results of this study found that these factors are Natural Resources, Human Resources, Public Services / Infrastructure, technology application, and Community Participation. Keywords : Economy; Village; Toba Lake